EXPERIMENTAL AND NUMERICAL INVESTIGATION OF SHORT-TERM BIODEGRADATION BEHAVIOR OF 3D PRINTED PLA - Ilhan, Recep; Senaysoy, Safa; Lekesiz, Huseyin (American Society of Mechanical Engineers, 2022)
There has been an increasing interest for biodegradable polymers in recent years because they can be formed as scaffolds and safely removed from the body without the need for any surgical operation, and contribute to the healing process. However, the main problem in polymer-based biodegradable materials is the inability to obtain tunable biodegradation behavior to match healing, which limits the clinical feasibility of these biomaterials. In this study, it is aimed to model biodegradation behavior from short term experimental data in an effort to reduce time required for determination of bio-degradation parameters. Thus, the degradation behavior can be determined and controlled at a lower cost. In this context, the biodegradation behavior of poly-lactic acid (PLA) polymer which is widely used in biomedical applications, was investigated experimentally and numerically on different days related to fracture bone healing times (5-12 weeks). First, 4.5 mm x 4.5 mm x 4.5 mm cubes were printed using the fused deposition modelling (FDM). Then, printed samples were exposed to degradation in the incubator by immersion in phosphate buffered saline (PBS) solution at 37 °C at physiological conditions for different time periods (0, 15, 30, 61 and 90 days). Throughout degradation, water absorption, weight loss, mechanical properties and morphological changes were investigated. Water absorption increases up to 13% within 61 days and then decreases to 10% within 90 days. On the other hand, samples gain 1% weight for the first 15 days and following, start losing weight around 0.3% percent at the end of 90 days. This clearly indicates that degradation occurs and water replaces the degraded material. There are fluctuations in the stiffness values that decrease on the 15 and 61 days but they increase on the 30th and 90th days. The increases in stiffness can be attributed to the compressive resistance of the trapped water content. Microscopic investigation clearly verifies the water content that the colors of the samples (opacity increase) changed while no significant change in its size occurred at different degradation days. Experimental results indicate a degradation and mechanical behavior variation throughout the process while dimensional stability during the 90 day degradation period. Numerical model predicts the stiffness values reasonably well within 15 and 30 days of degradation, but differences for 61 and 90 days. This difference possibly stems from the fact that the numerical model does not include any water inclusion disturbance. © © 2022 by ASME.
ASME 2022 17th International Manufacturing Science and Engineering Conference, MSEC 2022 -- 2022-06-27 through 2022-07-01 -- West Lafayette -- 183161
Keywords: additive manufacturing; Biodegradable biomaterials; computational model; in vitro degradation; poly-lactic acid